Judges' Consideration of Corruption Offenses that Return and Do Not Return Part of the State Financial Losses - Pramadina, Nadya; Ridlwan, Zulkarnain; Rosidah, Nikmah (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to mAnalyze the basis of the judge's consideration in resolving criminal acts of corruption against defendants who return and do not return state financial losses in Decision Number: 18/Pid.Sus-TPK/2022/PN.Tjk and 14/Pid.Sus-TPK/2023/PN .Tjk and analyze the sentences imposed by judges for criminal acts of corruption on defendants who return and do not return state financial losses in accordance with a sense of justice. The type of research used is normative research with a p approachlegislative, conceptual and case study approaches. The data used is primary data and secondary data.Data analysis was carried out using legal interpretation. The results of this research show that the basis for the judge's considerations in resolving criminal acts of corruption against defendants who return and do not return state financial losses judicially is that the defendant's actions are legally and convincingly proven to have committed the criminal act of corruption Article 3 Jo. Article 18 Paragraph (1) letter b of the Corruption Eradication Law.